Increasing Interest in Learning Social Studies in Early Grade Elementary Schools through Interactive Learning Methods in the Merdeka Curriculum - Livia Aliyah Alfita; Neng Nisa Audina Agustina; Riana Marthalivia Jauhar; Tin Rustini (Penerbit Hellow Pustaka, 2025)
Increasing students' interest in learning social studies in early elementary school through interactive learning methods can be done in several steps. Interactive learning method is an approach that uses interacting activities between teachers and students, as well as between students themselves. The use of interactive learning media such as videos, power points, and others can help increase students' interest in learning. This media can illustrate material with graphics, animation and various forms that can make learning more interesting and easy to understand. An interactive approach to social studies learning can help students achieve optimal learning outcomes. In the learning process, students can work together to complete tasks and show progress in interacting activities with their friends. Teachers also have wider opportunities to provide assistance. The blended learning method can improve the quality of student learning. In this learning process, students use digital and offline media simultaneously, which can make learning more effective and interesting.